Preliminary analysis of pacing strategies in a professional basketball - Kavaliauskas, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Pacing is the distribution of muscular work rate during exercise (Foster et al., 2004). Although pacing has been studied extensively in individual endurance sports, little research has investigated the distribution of work rates within team sports. The aim of this preliminary investigation was to analyse workload distribution of an individual player over the course of a basketball game. Methods: A professional male basketball player (small forward; age (years) - 24; height (cm) - 196; body mass (kg) - 85.2) from a British Basketball League team participated in this study. 1 digital video camera (Sony DRV900E) was used to film a home game which was replayed on SportsCode software for coding of activity patterns. Activities were coded based on five arbitrary locomotor categories in a horizontal direction (Dogramaci et al., 2011). Categories 0,1,2,3 and 4 corresponded to non-participation (i.e. substituted), stationary, walking, jogging, and sprinting respectively. Frequency of actions within each category were calculated for each quarter (Q1,2,3,4) of the match and the Coefficient of Variation (CV) was used to indicate the degree of variability in actions performed. Results: The player was active during Q1, Q2, and Q3 but did not participate in Q4. The frequency of category 1,2, and 3 actions was greatest in Q1, while the greatest frequency of category 4 activity (sprinting) occurred in Q2. Analysis of CV indicates that the degree of variability in total activity values decreased from 68.5%, to 46.5% and 45% through Q3, Q2 and Q3 respectively. Discussion: Pacing changes were observed throughout the game with less heterogeneous patterns occurring in the second and third quarters, largely due to the high frequency of periods when the player was engaged in lower intensity (category 1 and 2) activities in Q1. However, no `end-spurt` phenomenon could be identified since the player was substituted and did not play during Q4. Currently, there is little known about the exact mechanisms underpinning work rate distribution with a range of physiological, psychological and tactical factors potentially contributing to the selection and maintenance of different pacing strategies (St Clair Gibson et al., 2006). Match dynamics and positive emotional state may have affected the player`s pacing strategy with no reduction in work-rate as the match progressed because the team was winning. Therefore, further research examining pacing strategies during basketball is warranted.